Dynamic characterized genetic algorithm for adaptive beam forming in WCDMA system - Tiong, Sieh Keong; Ismail, Mahamod; Hassan, Azmi (IEEE, 2005)
In this paper, a modified Genetic Algorithm named as Dynamic Characterized Genetic Algorithm (DCGA) is proposed. The new DCGA is then integrated into adaptive beam forming technique to reduce the power usage of adaptive antenna at WCDMA base station (Node B) for serving instantaneous mobile needs. As contradict to conventional GA, DCGA is able to adapt itself in chromosome representation and number of crossover points in order to reduce unnecessary searching space and thus, increase convergence rate efficiently. Power usage at Node B is used as fitness function to compare the performance of DCGA and GA. Simulation result has shown that DCGA converges faster and is superior in adaptive beam forming in the aspect of power usage at Node B as compared to conventional GA